Radical Suffering, Callousness, and Child Abuse: Communal Responsibilities for Suffering and Advocacy within Cultures Abuse - Hood-Patterson, R. (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The definition of suffering is difficult to pinpoint, particularly when addressing suffering within cases of child abuse. Dividing humanity into the categories of “perpetrators” and “victims” is too rudimentary. This dichotomy depreciates the human cost of the “perpetrator” while simultaneously failing to account for the complexity of “victimization” and the communal/collective responsibility for the suffering of those abused. This essay introduces two terms from feminist Christian theology, “radical suffering” and “callousness,” as a way of bolstering already-established definitions of suffering within the clinical context and bioethics literature. The aim is to: a) describe suffering in a way that mitigates dehumanizing tendencies and b) direct attention to a collective responsibility for cultures of abuse that enable violence and violation.